PRINSIP DASAR RANCANG BANGUN EKONOMI ISLAM - Widyan, Linggawati (IAIN Ambon, 2021)
ABSTRACTThis article discusses how to formulate an Islamic economic design and the principles that form the basis of the economy. Although Islamic economics has several differences in its structure and sequence, in substance it is not much different, it is superior to other economies. There are basic principles in the design of Islamic economics. Some of these principles can generally be divided into three parts, namely: universal values, derivative principles and morals. Islamic economics is built on five universal Islamic values which are considered the foundations of Islamic economics including: ilahiyah, al-adl, an-nubuwah, al-khalifa and al-ma'ad. Then the derivative principles act as a pillar and consists of three principles including: multiple ownership, freedom to act and social justice. The last roof of the building is morals. Each of these parts forms a building and becomes a principle that can be used as an aspiration to formulate various theories in Islamic economics.Keywords: Islamic Economics, Basic Principles, Design ABSTRAKDalam artikel ini dibahas mengenai bagaimana rumusan dalam suatu rancang bangun ekonomi islam dan prinsip-prinsip yang menjadi landasan dalam perekonomian. Meskipun ekonomi islam memiliki beberapa perbedaan yang tersusun dalam struktur serta tata urutnya, akan tetapi secara subtansinya tidak jauh berbeda justru membuatnya lebih unggul daripada sisteem ekonomi yang lainnya. Terdapat prinsip-prinsip dasar dalam rancang bangun ekonomi islam. Beberapa prinsip tersebut secara umum dapat dibagi menjadi tiga bagian, yaitu: nilai-nilai universal, prinsip-prinsip derivatif dan akhlak. Ekonomi islam dibangun diatas lima nilai universal islam yang dianggap sebagai fondasi daalam eonomi islam diantaranya: ilahiyah, al-adl, an-nubuwah, al-khalifah dan al-ma’ad. Kemudian prinsip derifatif sebagai tiang penyangga dan terdiri dari tiga prinsip diantaranya: multiple ownership, freedom to act dan social justice. Terakhir atap dari bangunan tersebut adalah akhlak. Masing-masing bagian ini yang membentuk sebuah bangunan dan menjadi prinsip yang bisa dijadikan sebagai aspirasi untuk menyusun berbagai teori dalam ekonomi islam. Kata Kunci: Ekonomi Islam, Prinsip Dasar, Rancang Bangun